First University Chair of Lifestyle Medicine in Peru and Latin America: Primera Cátedra Universitaria De Medicina Del Estilo De Vida En Perú y Latinoamérica - De La Cruz-Vargas, Jhony A (2021)
Lifestyle Medicine is the new global medical discipline considered the seventh era of public health. 1,2 In 2004, the American College of Lifestyle Medicine emerged in the United States of America (https://www.lifestylemedicine.org/). In Europe, the European Organization for Lifestyle Medicine (https://www.eulm.org/) was created. Since 2014 the Latin American Association of Lifestyle Medicine (http://lalma.co/) has been working in more than 12 countries in the region. Currently, Lifestyle Medicine has a presence on five continents.